Things around us The child's first library of learning (Time life asia Hong Kong, 1989)
Summary: Things Around Us introduces young readers to the fascinating world of objects$1 (Bboth natural and man-made. The book explores how everyday things are created, used, and categorized. Through simple explanations, engaging questions, and colorful illustrations, it encourages children to observe their surroundings with curiosity and understand how human creativity and nature work together to shape the world. Abstract This educational volume in A Child's First Library of Learning aims to develop scientific thinking in early learners. It breaks down complex topics such as material science, manufacturing processes, and technology into digestible pieces for children. Through structured chapters and real-life examples, the book connects classroom concepts with real-world experiences, laying a strong foundation for understanding science and the environment. Review Things Around Us is a well-crafted introductory science book for children. The content is clear and accessible, with plenty of vibrant images and relatable analogies. Its strength lies in its interactive format$1 (Bquestions prompt thinking, while facts provide answers that are age-appropriate. Parents and educators have praised it for sparking curiosity and encouraging active learning through observation and discussion. A valuable resource for both home and school librariess
Title: Things Around Us Series: A Child's First Library of Learning Publisher: Time-Life Books Format: Hardcover, illustrated, educational non-fiction Contents: What Are Things? Things Made by Nature Things Made by People How Are Things Made? From Nature to Factory Different Kinds of Materials How Materials Are Used Machines That Make Things Buildings and Homes Transportation and Travel Communication Tools Things We Use Every Day Things for Fun and Play Taking Care of Things What Happens to Old Things?
Shelf A (A1)
Target Audience Note Ideal for children aged 4 to 8 years, this book is tailored for: Early learners curious about their surroundings Parents looking to introduce science in an engaging way Educators in preschool and primary settings Libraries building foundational STEM collections.
Keywords: English - Refrence; Earth; World culture; Human geography; Everyday life; Environmental awareness; Children$1 (Bs questions and answerss